2018
DOI: 10.1002/cpe.4789
|View full text |Cite
|
Sign up to set email alerts
|

IoT and semantic web technologies for event detection in natural disasters

Abstract: Summary Natural disasters cannot be predicted well in advance, but it is still possible to decrease the loss of life and mitigate the damages, exploiting some peculiarities that distinguish them. Smart collection, integration, and analysis of data produced by distributed sensors and services are key elements for understanding the context and supporting decision making process for disaster prevention and management. In this paper, we demonstrate how Internet of Things and Semantic Web technologies can be effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Event detection backed by IoT sensor data and social media streams can detect any incident within the first few seconds of its occurrence [47]. Pattern recognition mechanism offers the machine learning ability to detect the useful patterns of information from textual or spatial data sets crucial for disaster management [48]. Semantic engine can be utilized for effective information management, i.e., categorizing, searching and extracting of unstructured information.…”
Section: ) Data Analytics and Management Layermentioning
confidence: 99%
“…Event detection backed by IoT sensor data and social media streams can detect any incident within the first few seconds of its occurrence [47]. Pattern recognition mechanism offers the machine learning ability to detect the useful patterns of information from textual or spatial data sets crucial for disaster management [48]. Semantic engine can be utilized for effective information management, i.e., categorizing, searching and extracting of unstructured information.…”
Section: ) Data Analytics and Management Layermentioning
confidence: 99%
“…IoT offers smart aggregation, integration, and analysis of multi-dimensional and multi-sourced data, which are the main steps for situational awareness for effective decision-making. In a study [37] the authors demonstrated how IoT with semantic web technologies can be successfully deployed for earthquakerelated event detection. The proposed system was able to semantically annotate streams that were retrieved from web services gathering IoT-based sensors data for effective earthquake event detection.…”
Section: B From Wsn To Iot For Disaster Managementmentioning
confidence: 99%
“…With the new generation of information technology, Internet of Things (IoT) has developed rapidly and has been applied to support applications in various fields such as environmental protection and military monitoring [1], [2]. IoT nodes connect and communicate with each other through sensing and perception.…”
Section: Introductionmentioning
confidence: 99%